Difficulties in Developing the Diagnostic Competence of Nursing Students At My Youssef Hospital in Casablanca: Descriptive Study - Brahim Darraj,; Bouchra Gourja,; Abderrazak Faiq,; El Mostafa Tace,; Said Belaaouad, (Iraqi Journal of Science, 2021)
This descriptive research aims atidentifying the difficulties encountered by nursing students in the development of nursing diagnostic skills. The data collection was carried out using a direct questionnaire with 62 students in My Youssef’s hospital in Casablanca. The results of the study list a set of failures related to the training of nurses. This training focuses mainly on the acquisition of knowledge; it is not aimed to the development of the real skill.